Hubungan Aktivitas Fisik dengan Status Kesehatan Hipertensi pada Lanjut Usia - Budiono Budiono; Hartati Hartati; Handoyo Handoyo; Rina Saraswati (Prodi Keperawatan Purwokerto, Poltekkes Kemenkes Semarang, 2025)
Background: Diseases or health disorders in old age are generally chronic and degenerative, such as hypertension. Hypertension is greatly influenced by many factors. One of the factors that influences the occurrence of hypertension is physical activity. Regular exercise can stimulate the release of endorphins, which cause euphoria and muscle relaxation effects, so that blood pressure does not increase. Objective: This research aims to identify the relationship between physical activity and hypertension health status in the elderly in Ngabean Village, Mirit District, Kebumen Regency. Method: This study uses a descriptive analytical method with a cross-sectional approach. The sample consisted of 54 elderly residents who were taken purposively. The data were analyzed descriptively and correlatively using Chi Square. Results: Based on the research conducted, it was found that most respondents (50.0%) in Ngabean Village, Mirit District, Kebumen Regency were in the moderate physical activity category. Most respondents (57.4%) in Ngabean Village, Mirit District, Kebumen Regency had normal blood pressure. Conclusion: There is a positive relationship between physical activity and hypertension health status in the elderly in Ngabean Village, Mirit District, Kebumen Regency (p =0.013).